Directions of Price Transmission on the Diesel Oil Market in Poland - Grzegorz Przekota; Anna Szczepańska-Przekota (Energies)
The formation of crude oil prices and their impact on diesel prices represent a significant economic challenge. The economy’s dependence on energy resources means that the development and competitiveness of the economy, as well as the standard of living of society, are contingent upon energy prices, including those of liquid fuels. It is therefore important to recognise the process by which changes in the price of crude oil affect other commodities. The recognition of these dependencies will have implications for political and fiscal decision-making at the governmental level, investment strategies of enterprises, and patterns of consumption. The research presented in this paper concerns the transmission of crude oil prices and the wholesale and retail prices of diesel oil in Poland between 2010 and 2024. A correlation analysis, a Granger causality test, and an impulse response function calculation were conducted. The research demonstrated that crude oil prices are the cause of the formation of wholesale and retail prices of diesel oil. However, the causality between wholesale and retail prices is bilateral, with a stronger flow of impulses from retail prices to wholesale prices than vice versa. These findings have significant implications for the evolution of the retail market. While the current situation may lead to the monopolisation of the market, it also provides decision-makers with the ability to regulate the market, potentially reducing the volatility of retail prices relative to raw material quotations. Furthermore, it offers a means to safeguard the retail market against speculative activities and mitigate the impact of sudden increases in raw material prices.